All-Inside Partial Epiphyseal Anterior Cruciate Ligament Reconstruction Plus an Associated Modified Lemaire Procedure Sutured to the Femoral Button - Leyes Vence, Manuel; Roca Sanchez, Tomas; Flores Lozano, Cesar; Villarreal Villareal, Gregorio (Elsevier, 2019)
Anterior cruciate ligament (ACL) tears in skeletally immature patients are on the rise; pediatric athletes are now in constant year-round sports participation. Nonoperative treatment may lead to poor functional outcomes and an increase in associated intra-articular lesions and sometimes can cause drop-out from sports activity. The treatment of these injuries is not at all clear, and appropriate guidelines do not exist. Physeal-sparing and partial physeal-sparing techniques have been described. Concerns about restoring normal knee kinematics with the previously described ACL reconstruction (ACLR) techniques are open to debate. We describe a partial epiphyseal ACLR to be done in skeletally immature patients involved in highly demanding sport activities. This technique is performed with an extraphyseal femoral tunnel drilled retrograde, a transphyseal tibial tunnel, and a retrograde tibial drilling without trespassing the tibial physis. We added a modified Lemaire procedure to improve rotational instability to the previously performed ACLR.